Promoting speaking spontaneity in large classes: An action research study in an Indonesian EFLuniversity setting - Ramdani, Junjun Muhamad; Rahmat, R. (Universitas Pendidikan Indonesia, 2018)
In the last two decades, teaching spoken English to EFL students has become a critical issue in the TESOL context. However, a few studies touch upon how EFL learners are taught to speak English spontaneously. Learning to speak English spontaneously in large classes becomes a big challenge for ESOL teachers because of space and time constraints. In response to this growing need, this article provides an empirical account of how modified role playing, more student-centered learning, is implemented as an innovative learning design in an EFL university setting where a large class is concerned. Data were garnered from open-ended and close-ended questionnaires, students’ personal narratives, and photovoices. These data were analyzed using Interpretative Phenomenological Analysis (IPA). Findings of the study show that the students were finally able to survive in their speaking tasks, engaging them in a real-life communicative encounter. This study concludes with some pedagogical implications for how a teacher as a curriculum designer engages students in motivating and anxiety-free speaking tasks.